PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH KENAKALAN REMAJA - Putra, Ilham Andika; Wahyuni, Sri Pulan (Al Naqdu, 2025)
Cases of juvenile delinquency such as the use of offensive language, truancy, and disrespectful behavior toward teachers are frequently encountered at SMP Negeri 2 Singkep. Addressing these issues requires serious attention from parents, the community, and particularly the school. Within the school context, Islamic education teachers hold a pivotal role in instilling religious values and fostering students’ moral and character development. This study employs a qualitative fieldwork approach, with data collected through observation, interviews, and documentation. The findings reveal: (1) the contributing factors to juvenile delinquency include family conditions, environmental influences, and social media exposure; and (2) the roles of Islamic education teachers in preventing delinquency encompass five dimensions—educator, mentor, motivator, role model, and facilitator of religious activities. These results highlight the strategic importance of Islamic education teachers in guiding students toward positive behavior and moral integrity.